Application of Financial Statements Based on Financial Accounting Standards for Micro, Small and Medium Entities in Citrus MSMEs Pressing Pak Ali - Lidia Arlini Nasution; Junawan (International Journal of Management, Economic and Accounting, 2025)
This research was carried out on Pak Ali's Orange MSMEs in Medan City with the aim of analyzing the application of the preparation of financial statements based on SAK EMKM. This study uses a qualitative descriptive approach with data collection techniques in the form of literature studies, interviews, observations, and documentation. The data used consisted of primary data and secondary data. The results of the study show that Pak Ali's Orange MSMEs have not implemented financial recording in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) because business owners still do not understand these standards. Some of the obstacles faced include the owner's lack of understanding of SAK EMKM, the assumption that the preparation of financial statements is not important, and the absence of employees who have an accounting background. In addition, the absence of socialization from related agencies causes business owners to not realize the importance of implementing SAK EMKM. As a result, financial recording is still simple and only includes sales transactions, revenues, expenses, and profits without the preparation of income statements, financial position statements, and records of financial statements in accordance with applicable accounting standards.